Transmission risk of two chikungunya lineages by invasive mosquito vectors from Florida and the Dominican Republic. - Barry W Alto; Keenan Wiggins; Bradley Eastmond; Daniel Velez; L Philip Lounibos; Cynthia C Lord (Public Library of Science (PLoS), 2017)
Between 2014 and 2016 more than 3,800 imported human cases of chikungunya fever in Florida highlight the high risk for local transmission. To examine the potential for sustained local transmission of chikungunya virus (CHIKV) in Florida we tested whether local populations of Aedes aegypti and Aedes albopictus show differences in susceptibility to infection and transmission to two emergent lineages of CHIKV, Indian Ocean (IOC) and Asian genotypes (AC) in laboratory experiments. All examined populations of Ae. aegypti and Ae. albopictus mosquitoes displayed susceptibility to infection, rapid viral dissemination into the hemocoel, and transmission for both emergent lineages of CHIKV. Aedes albopictus had higher disseminated infection and transmission of IOC sooner after ingesting CHIKV infected blood than Ae. aegypti. Aedes aegypti had higher disseminated infection and transmission later during infection with AC than Ae. albopictus. Viral dissemination and transmission of AC declined during the extrinsic incubation period, suggesting that transmission risk declines with length of infection. Interestingly, the reduction in transmission of AC was less in Ae. aegypti than Ae. albopictus, suggesting that older Ae. aegypti females are relatively more competent vectors than similar aged Ae. albopictus females. Aedes aegypti originating from the Dominican Republic had viral dissemination and transmission rates for IOC and AC strains that were lower than for Florida vectors. We identified small-scale geographic variation in vector competence among Ae. aegypti and Ae. albopictus that may contribute to regional differences in risk of CHIKV transmission in Florida.